Prevalence of vocal tract discomfort in patients with voice disorders - Nawaz, Saffa; Shahid, Nameeka; Mumtaz, Nazia; Saqulain , Ghulam (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse the prevalence of vocal tract discomfort in patients with voice disorders. Method: The analytical cross-sectional study was conducted at Riphah International University, Lahore, Pakistan, from September 2020 to January 2021, and comprised voice disorder patients of either gender aged 18-65 years enrolled from Mayo Hospital, Sheikh Zayed Hospital and Jinnah Hospital, Lahore. The Vocal Tract Discomfort Scale was used for data-collection. Data was analysed using SPSS 21. Results: Of the 137 patients, 68(49.6%) were males and 69(50.4%) were females. The overall mean age was 36.36±12.47 years. The most affected age group was 18-33 years 70(51.1%) while those aged 50-65 years were the least affected 28(20.4%). The most common VTD symptom was dryness with mean frequency 3.48±1.97 and mean severity 3.36±1.99, followed by irritation 2.88±2.08 and 2.88±2.12, and lump in the throat 2.42±2.27 and 2.31±2.23, respectively. Conclusion: Dryness, irritation and a lump in the throat were the most common symptoms of vocal tract discomfort. Keywords: Dysphonia, Vocal tract discomfort, Voice disorders.